An Overview of Illegal Logging Situation in Peninsular Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2013)
The trends of illegal logging and current situation of illegal logging in Peninsular Malaysia were studies. Data and information from year 2001 to 2010 on volume of log productions (m3) and volume of illegal log productions were collected from the government and private sectors such as the Forestry Department Peninsular Malaysia (FDPM), International Tropical Timber Organization (ITTO) and Food and Agriculture Organization (FAO). The data obtained were statistically analyzed using the correlation analysis to determine the direction and the strength of the relationship between log productions and illegal log productions. The results showed that the trends of illegal logging are on the increased. Eighteen percents (18%) of the logs cut annually are obtained from illegal operation. The log productions and illegal log productions resulted have a weak negative relationship as r = -0.271, p = 0.603 and do not significantly related. The illegal log productions are inversely related with the log productions. It can be concluded that the log productions in Peninsular Malaysia occurred in a small scale and the situation is under control. Proper long-term planning needs to be generated and implemented to prevent the problem from becoming worse.
Keywords: Log productions; Illegal logging; Trend analyzed; Peninsular Malaysia